2021
DOI: 10.1016/j.clindermatol.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A dermatologic perspective on multisystem inflammatory syndrome in children

Abstract: As of May 2020, an emerging immune-mediated syndrome primarily affecting children has been detected primarily in Europe and the United States. The incidence of this syndrome appears to mirror the initial infectious assault, with a delay of several weeks. This syndrome has been termed multisystem inflammatory syndrome in children (MIS-C), and is observed in association with the coronavirus disease 2019 (COVID-19). The phenotypes of presentation include several characteristic features, including prolonged fever,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 33 publications
3
33
0
5
Order By: Relevance
“… Study Design Data Collection Date Sample n= Age, y, Location of oral lesions Type of oral lesions PIMS-TS Ahmed et al (2020), USA [ 10 ] SR Jan–July 2020 662 (39 studies) Mean 9.3 ± 0.5 Lips, Tongue Cheilitis (n = 216, 32.6%) Tongue Swelling (n = 31, 4.7%) Yes Bhujel et al(2021) UK [ 3 ] SR Mar 2020 84 (3 studiesreported paediatric patients) Range 3 months to 20 years Tongue, lip Oral pseudomembranous candidiasis (n = 2, 2%) Geographic tongue (n = 1, 1%) Coated tongue (n = 2, 2%), Red or swollen lips (n = 23, 27%) Strawberry tongue= (n = 5, 6.0%), Oral cavity changes unspecified (n=16, 19.0%) Yes (2 studies) (Falah et al, 2020 & Halepas al. 2021) Naka et al (2021), USA [ 11 ] Review article Jan 2021 452 (8 case series) Median 8 to 12 Oral mucosa and lips Dry and red lips and/or other mucosal changes in 25%–87% in children with MIS-C (n=185 affected) Yes Rekhtman et al (2020), USA [ 12 ] Cohort May 2020 31 (M: 19, F:11) Range 1.75 to 16 Tongue, Lips MIS-C group: Lip fissuring (n=4, 21%), tongue papillitis (n=2, 11%) COVID-19 group: Lip fissuring (n=1, 8%) Yes Whittaker et al (2020), Europe & USA [ 13 ] CS Mar–May 2020 58 Median 9 Lips Mucous membrane changes and red cracked lips (n = 11, 25%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Study Design Data Collection Date Sample n= Age, y, Location of oral lesions Type of oral lesions PIMS-TS Ahmed et al (2020), USA [ 10 ] SR Jan–July 2020 662 (39 studies) Mean 9.3 ± 0.5 Lips, Tongue Cheilitis (n = 216, 32.6%) Tongue Swelling (n = 31, 4.7%) Yes Bhujel et al(2021) UK [ 3 ] SR Mar 2020 84 (3 studiesreported paediatric patients) Range 3 months to 20 years Tongue, lip Oral pseudomembranous candidiasis (n = 2, 2%) Geographic tongue (n = 1, 1%) Coated tongue (n = 2, 2%), Red or swollen lips (n = 23, 27%) Strawberry tongue= (n = 5, 6.0%), Oral cavity changes unspecified (n=16, 19.0%) Yes (2 studies) (Falah et al, 2020 & Halepas al. 2021) Naka et al (2021), USA [ 11 ] Review article Jan 2021 452 (8 case series) Median 8 to 12 Oral mucosa and lips Dry and red lips and/or other mucosal changes in 25%–87% in children with MIS-C (n=185 affected) Yes Rekhtman et al (2020), USA [ 12 ] Cohort May 2020 31 (M: 19, F:11) Range 1.75 to 16 Tongue, Lips MIS-C group: Lip fissuring (n=4, 21%), tongue papillitis (n=2, 11%) COVID-19 group: Lip fissuring (n=1, 8%) Yes Whittaker et al (2020), Europe & USA [ 13 ] CS Mar–May 2020 58 Median 9 Lips Mucous membrane changes and red cracked lips (n = 11, 25%) …”
Section: Resultsmentioning
confidence: 99%
“…The most commonly affected oral sites were the lips and tongue and the most commonly reported symptoms were cheilitis, dry and red mucosal membranes, and tongue swelling. The studies also identified ‘oral mucosal changes’ in a large number of the study population, however the specific changes were not mentioned and therefore cannot be compared to the rest of the data [ 11 ]. Two of the five studies included in this review were systematic reviews, the first reported on oral lesions in patients with COVID-19 [ 3 ] and the second one reported on PIMS-TS [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pediatric population, one interesting condition (multisystem inflammatory syndrome in children) is being increasingly reported; wherein the cutaneous manifestations have been found to simulate Kawasaki disease. [ 4 ]…”
mentioning
confidence: 99%
“…4 Multisystem inflammatory syndromes which simulate Kawasaki disease were commonly seen in the pediatric population. 5 There is scarcity of data regarding cutaneous manifestation of COVID-19 from Nepal, a case report of Erythema multiforme like lesion has been reported. 6 As the COVID-19 pandemic picked up the threads, many of the cutaneous manifestations reported could be explained by the "Baader-Meinhof phenomenon" which Date of Submission: 19 th June, 2021 Date of Acceptance: 30 th August, 2021 Date of Publication: 1 st October 2021 is a frequency illusion and regarded as cognitive bias in which, there is a tendency to notice more frequently after noticing for the first time leading to selection bias.…”
mentioning
confidence: 99%